Rekayasa Kinerja Campuran Asphalt Concrete Wearing Course (AC-WC) Berbasis Limbah Biomassa: Studi Eksperimental Modifikasi Palm Kernel Shell dan Dammar Resin terhadap Karakteristik Marshall dan Parameter Volumetrik - Danang Wahyu kurniawan; Fathul Hidayat AR Rizqi; Rachmat Mudiyono (Journal of Engineering and Applied Technology, 2026)
Asphalt Concrete Wearing Course (AC-WC) road pavement functions as a crucial wearing layer to maintain its performance and service life, but conventional asphalt still faces problems with its high cost and dependence on non-renewable natural resources. Therefore, this study analyzes the use of palm kernel shell waste and dammar resin as a modified AC-WC mixture, looking at its Marshall characteristics and suitability to Bina Marga specifications. The method used is an experimental laboratory with variations of palm kernel shells of 0%, 2.5%, 5%, 7.5% plus dammar resin of 0%, 2%, 4%, and 6%. Marshall tests check stability, flow, VIM, VMA, VFA, and MQ according to SNI and Bina Marga. The results show that the addition of both has a positive effect, with the optimum at 7.5% palm kernel shells and 6% dammar resin increasing stability and meeting technical standards, making it highly potential as an environmentally friendly and cost-effective alternative